2021
DOI: 10.1097/nne.0000000000001141
|View full text |Cite
|
Sign up to set email alerts
|

A Transformative Learning Experience for Senior Nursing Students

Abstract: Background: Research suggests that clinical practicums in hospital-based settings are important, even if condensed, to provide students with the opportunity for real-world learning experiences. Rational dialogue makes learning meaningful and empowers students to learn by reflecting on experiences. Problem: The COVID-19 pandemic minimized availability of traditional one-to-one mentorship practicums. Approach: This article describes the use of critical reflection on experiences in an undergraduate senior men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…The study by Revell et al (2022) [ 26 ] disclosed the results of supplementing the traditional clinical period with an 18-h simulated experiences pack ( Table 2 ). The authors revealed the evidence of transformative learning expressed by students.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study by Revell et al (2022) [ 26 ] disclosed the results of supplementing the traditional clinical period with an 18-h simulated experiences pack ( Table 2 ). The authors revealed the evidence of transformative learning expressed by students.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings show that nursing schools made an effort to replace traditional clinical training with several activities, primarily based on simulation or virtual activities, allowing students to improve their abilities in caretaking [ 17 , 18 , 21 , 24 , 25 , 27 , 28 ]. Simulation sessions were structured in steps, with suggested reading, pre- and post-simulation quizzes, interactive clinical scenarios, and reflection [ 25 , 26 ]. They improved communication skills by role-playing, gaining experience in practical activities, and flipping clinical practice to replicate traditional care [ 17 , 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations